2019
DOI: 10.1177/1129729819845991
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with outcome after successful radiological intervention in arteriovenous fistulas: A retrospective cohort

Abstract: Introduction:Arteriovenous fistulas are the best form of vascular access for haemodialysis. A radiological balloon angioplasty is the standard treatment for a clinically relevant stenosis, but the recurrence rate is high. Data on factors associated with recurrence are limited.Methods:A single centre, retrospective analysis was performed for 124 consecutive patients who had successful interventions for dysfunctional arteriovenous fistulae, to examine factors associated with post-intervention patency. Follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
11
2
Order By: Relevance
“…In the present study, we demonstrated that blood flow volume after PTA was an important factor associated with primary patency after PTA. Previous studies found that primary patency after PTA was associated with AVF age, [5][6][7][8] upper arm AVF, 18 hypertension, 19 lesion length, 7,20 vessel disease score (a composite variable of diabetes, coronary artery disease, and peripheral vascular disease), 20 thrombosis, 8 diabetes, 9 asymmetrical dimethylarginine level, 9 low-density lipoprotein level, 9 calcium phosphate product, 19 urea reduction ratio, 19 and albumin level. 19 Almost no reports on primary patency after PTA mention blood flow volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we demonstrated that blood flow volume after PTA was an important factor associated with primary patency after PTA. Previous studies found that primary patency after PTA was associated with AVF age, [5][6][7][8] upper arm AVF, 18 hypertension, 19 lesion length, 7,20 vessel disease score (a composite variable of diabetes, coronary artery disease, and peripheral vascular disease), 20 thrombosis, 8 diabetes, 9 asymmetrical dimethylarginine level, 9 low-density lipoprotein level, 9 calcium phosphate product, 19 urea reduction ratio, 19 and albumin level. 19 Almost no reports on primary patency after PTA mention blood flow volume.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported factors associated with VA patency include time since VA construction and diabetes. [5][6][7][8][9] In the present study, we investigated blood flow volume using ultrasonography before and after PTA, which has not been sufficiently studied, as well as factors previously found to be correlated with primary patency after the initial PTA following shunt construction in patients with AVF.…”
mentioning
confidence: 99%
“…The 6-month TLPP in the control group was 84.5% in the current trial, and this is higher than those reported in the other published trials 20,22 and most institutional case series. [4][5][6][7][8][9][10] The TLPP in the control arm of the study by Lookstein et al was only 59.5% at 6 months. 22 This underlines the value of a good balloon fistuloplasty in maintaining patency.…”
Section: Discussionmentioning
confidence: 92%
“…This is unlikely to explain the lower event rate in the current trial because previous data suggest that postintervention access circuit primary patency is similar in patients with multiple or single lesions. 7 However, stenoses at multiple sites in the access circuit are a common finding, and deciding which is clinically most significant can be subjective. We therefore only included patients with a stenosis at a single site in the circuit to be sure that this lesion was responsible for the clinical problem leading to intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation